(untitled) (Baghdad Science Journal, 2018)
A new copolymer (MFA) was prepared from condensation of melamine (M) with p- methyl – anisole (A) in the presence of condensation agent like 37% (w/v) of formaldehyde. The new copolymer was characterized by elemental, IR and HNMR spectra. The chelating ion-exchange property of this polymer was studied for methylene blue dye in aqueous solution in 100-200ppm concentrations. The adsorption study was carried out over a wide range of pH, shaking time and in media of various kinetic parameters models. Thermal parameters like enthalpy, entropy and Gibbs free energy of adsorption process of methylene blue on surface of MFA resin were determined on the basis of kinetic parameters at different temperatures. To describe the equilibrium of adsorption, the Langmuir, Freundlich and Temkin isotherms were used. The Langmuir isotherm correlation (R2=0.987) was the best fitted for experimental data with maximum adsorption capacity of 200 ppm. A higher correlation value of the kinetic’s model was observed close to pseudo first order, second order and Temkin kinetic models values of correlation R2 lie in the range (0.983-0.987) in comparing to other kinetic models.